Hubungan Interaksi Sosial dengan Kualitas Hidup Lansia di Kelurahan Korong Gadang Kecamatan Kuranji Kota Padang - Rahmah, Siti Masyithah (E-Jurnal Medika Udayana; Vol 13 No 4 (2024): E-Jurnal Medika Udayana, 2024)
Increased life expectancy has resulted in an increase in the number of elderly people. Over time, the various organ systems of the elderly body undergo changes that cause them to have limitations in activities so that they are considered as helpless individuals and slowly withdraw from society. This results in a decrease in social interaction which will affect the quality of life of the elderly. This study aims to determine the relationship between social interaction and the quality of life of the elderly in Korong Gadang Village, Kuranji District, Padang City. This study is an observational analytic study with a cross sectional design. Data were collected by guided interviews using the social interaction questionnaire and the OPQOL-35 quality of life questionnaire with 60 respondents. Respondents had good social interaction (86.7%) and good quality of life (80.0%). The results of bivariate analysis using the Chi-square statistical test showed a p value = 0.043 (p <0.05). The conclusion of this study is that there is a relationship between social interaction and the quality of life of the elderly in Korong Gadang Village, Kuranji District, Padang City. Keywords : elderly, social interaction, quality of life